FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELENGKAPAN PENDOKUMENTASIAN ASUHAN KEBIDANAN DI RSUD HASANUDDIN DAMRAH MANNA - Tria Nopi Herdiani (STIKes CHMK, 2020)
The documentation in the Indonesian dictionary is a written / printed letter that can be used as evidence (such as birth certificate, marriage certificate, treaty, etc.). The purpose of this study is known to the relationship of factors (knowledge, education and years of service) with the completeness of documentation of midwifery care at Hasanuddin Damrah Hospital in Manna, Bengkulu Selatan Regency. This research is an Analytical Survey research with cross sectional design method. The population in this study were all midwives in RSUD Hasanuddin Damrah Manna, totaling 138 people. Samples were taken using a purposive sampling technique totaling 38 people. Collecting data using primary data that is direct observation and questionnaires distributed to midwives in RSUD Hasanuddin Damrah Manna Kabupaten Bengkulu Selatan and secondary data collected from the room documentation and patient status in RSUD Hasanuddin Damrah Manna Kabupaten Bengkulu Selatan. Analysis using the chi-square test and linear logistic regression (logistic regression linear). The results showed the completeness of documentation of midwifery care at Hasanuddin Damrah Hospital in Bengkulu Selatan Regency in the complete category of 22 respondents, knowledge of midwives in the good category of 21 respondents, midwife education in the academic category of 25 respondents, the working period of midwives in the old category of 25 respondents. There is a relationship of knowledge and education with the completeness of documentation of midwifery care and there is no relationship of work period with the completeness of documentation of midwifery care at Hasanuddin Damrah Hospital in South Bengkulu Regency. It is hoped that the hospital can emphasize the importance of completing patient medical documentation because it is very useful to know the patient's history in the future as well as accountability if there are problems regarding the actions given in the future by conducting seminars or training in completing midwifery documentation. It is hoped that midwives can improve their abilities through seminars and workshops on midwifery documentation.